Hidden talents in harsh conditions? A preregistered study of memory and reasoning about social dominance. Issue 4 (16th May 2019) - Frankenhuis, Willem E.; de Vries, Sarah A.; Bianchi, JeanMarie; Ellis, Bruce J.
Abstract: Although growing up in stressful conditions can undermine mental abilities, people in harsh environments may develop intact, or even enhanced, social and cognitive abilities for solving problems in high‐adversity contexts (i.e. 'hidden talents'). We examine whether childhood and current exposure to violence are associated with memory (number of learning rounds needed to memorize relations between items) and reasoning performance (accuracy in deducing a novel relation) on transitive inference tasks involving both violence‐relevant and violence‐neutral social information (social dominance vs. chronological age). We hypothesized that individuals who had more exposure to violence would perform better than individuals with less exposure on the social dominance task. We tested this hypothesis in a preregistered study in 100 Dutch college students and 99 Dutch community participants. We found that more exposure to violence was associated with lower overall memory performance, but not with reasoning performance. However, the main effects of current (but not childhood) exposure to violence on memory were qualified by significant interaction effects. More current exposure to neighborhood violence was associated with worse memory for age relations, but not with memory for dominance relations. By contrast, more current personal involvement in violence was associated with better memory for dominance relations, but not with memory for age relations. These results suggest incomplete transfer of learning and memory abilities across contents. This pattern of results, which supports a combination of deficits and 'hidden talents, ' is striking in relation to the broader developmental literature, which has nearly exclusively reported deficits in people from harsh conditions. A video abstract of this article can be viewed at: https://youtu.be/e4ePmSzZsuc . Abstract : People who grow up in stressful conditions may develop 'hidden talents': intact, or even enhanced, abilities for solving problems in high‐adversity contexts. We find partial support for this hypothesis. In our study, more current exposure to violence predicts intact or even enhanced memory for social dominance relationships, but more childhood exposure to violence predicts impaired memory for social dominance relationships.